Congenital Adrenal Hyperplasia: A Review of Current Knowledge and Future Directions - Zuzanna Szczepaniak; Agata Konopka; Natalia Wdowiak; Karina Lissak; Małgorzata Komarów; Martyna Choinka; Dominika Karasińska; Jakub Kalisiak (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Congenital adrenal hyperplasia (CAH) is a group of diseases in which genetic defects occur that disturb the synthesis of cortisol. The most common variant of CAH (95%-99%) is caused by 21-hydroxylase deficiency as a result of mutations in the CYP21A2 gene and is one of the most common monogenic diseases. CAH is characterized by androgen overproduction along with variable degrees of cortisol and aldosterone deficiency. Age at diagnosis can provide some information about the underlying mutations, with those diagnosed at birth/early infancy being at greater risk of developing serious enzyme defects. Classic and non-classical forms of this disorder have been described in the literature. CAH diagnosis is based on the clinical presentation, hormonal panel, Adrenocorticotropic Hormone (ACTH) stimulation test, and genetic testing. The main goals of treatment for congenital adrenal hyperplasia are glucocorticoid/mineralcorticoid supplementation, control of high adrenal androgen levels, fertility control, genetic counseling, and optimization of patients' quality of life. Purpose of the work: This study aims to review and characterize the clinical and pathophysiological aspects of congenital adrenal hyperplasia. Materials and methods: A comprehensive analysis of research papers available on PubMed, Google Scholar, Web of Science, Embase and Scopus was undertaken using the searchterms encompassing the following keywords: congenital adrenal hyperplasia, 21-hydroxylase deficiency, CYP21A2 Results: Congenital adrenal hyperplasia is a heterogeneous group of genetic disorders that can lead to serious and even fatal complications in the form of adrenal crisis. Therefore, screening tests and early diagnosis are crucial and can save the lives of newborns. Treatment should be individualized and allow patients to achieve normal growth, sexual development, fertility and a better quality of life.